NTM stabilization by alternating O-point EC current drive using a high-power diplexer. (31st August 2016) - Kasparek, W.; Doelman, N.; Stober, J.; Maraschek, M.; Zohm, H.; Monaco, F.; Eixenberger, H.; Klop, W.; Wagner, D.; Schubert, M.; Schütz, H.; Grünwald, G.; et al.
Abstract: At the tokamak ASDEX Upgrade, experiments to stabilize neoclassical tearing modes (NTMs) by electron cyclotron (EC) heating and current drive in the O-points of the magnetic islands were performed. For the first time, injection into the O-points of the revolving islands was performed via a fast directional switch, which toggled the EC power between two launchers synchronously to the island rotation. The switching was performed by a resonant diplexer employing a sharp resonance in the transfer function, and a small frequency modulation of the feeding gyrotron around the slope of the resonance. Thus, toggling of the power between the two outputs of the diplexer connected to two articulating launchers was possible. Phasing and control of the modulation were performed via a set of Mirnov coils and appropriate signal processing. In the paper, technological issues, the design of the diplexer, the tracking of the diplexer resonance to the gyrotron frequency, the generation and processing of control signals for the gyrotron, and the typical performance concerning switching contrast and efficiency are discussed. The plasma scenario is described, and plasma experiments are presented, where the launchers scanned the region of the resonant surface continuously and also where the launchers were at a fixed position near to the q   =  1.5-surface. In the second case, complete stabilization of a 3/2 NTM could be reached. These experiments are also seen as a technical demonstration for the applicability of diplexers in large-scale ECRH systems.